Motility and Viability of Kampung Chicken Sperm Using Diluents Containing Glycine and Glucose - Salam, La Ode Muhammad Aswad; Zulkarnain, La Ode Muhammad Iskandar; Ramadhani, Rani; Junaedi, Junaedi; Khaeruddin, Khaeruddin (Tarjih Tropical Livestock Journal, 2025)
The success of an artificial insemination program in native chickens is largely determined by the quality of liquid semen used during storage. This study aimed to evaluate the effect of diluents containing 30 mM glucose, 30 mM glycine, and a combination of both on the motility and viability of native chicken liquid semen stored at 3-5°C. The study used a Completely Randomized Design (CRD) with four treatments: control, 30 mM glucose, 30 mM glycine, and a combination of 30 mM glucose-glycine, each with five replications. Fresh semen from three native roosters aged 10-14 months was collected using the massage method, then diluted with a Ringer's lactate-egg yolk-based diluent at a ratio of 1:5. Evaluation of spermatozoa motility and viability was carried out daily for three days of storage. Data were analyzed using ANOVA followed by Duncan's Multiple Range Test at a significance level of 5%. The results showed that on the first day, all treatments had motility 75.76-75.85% and viability 87.03-88.32% which were not significantly different (P>0.05). On the second and third days, the 30 mM glycine treatment and combination showed significantly higher motility 42.02-42.20% and 33.19-33.22% respectively, and viability 67.87-67.92% and 57.89-57.90% respectively compared to the control and single glucose. The 30 mM glucose treatment did not show any superiority over the control. It was concluded that 30 mM glycine supplementation, either alone or in combination with glucose, effectively maintained the quality of native chicken liquid semen for up to three days of storage through osmoprotection and antioxidative mechanisms.